Migrant narratives: Reading literary representations of Christian migration in Kerala, 1920 -70 - Varghese, VJ (The Indian Economic and Social History Review, 43, 2 (2006), 2006)
The population movements that have occurred within present-day Kerala should be seen in tandem with the history of the massive out-migration record of the state, which has earned for its people the image of being a robust community with a proclivity for migration. This article explores the fashioning of the figure of the kutiyettakkaran, a migrant, in the Malayalee unconscious by problematising the peasant migration from Travancore to Malabar during 1920.70. Reading across Malayalam literary representations, this article looks at the configuration of the migrant self as located within the problematic of capital and colonial modernity. These literary texts, simultaneously fashioned by and fashioning history, give a nuanced picture of the contradictions and compulsions that governed the migrants as well as the natives. The migrant identity of the Syrian Christian settler in Malabar is construed within a social imaginary regulated by a specific discourse of development. The fashioning and circulation of a modernising and heroic image endowed the migrant with a peculiar authority in the landscape and history of Malabar. However, such a mission is critiqued, often in absolute terms, by texts closer to our times. These contemporary texts, informed as much by the consequences of the migration, play an important role in reconfiguring the Syrian Christian migrant as a stooge of capital.